SPORT WATER RESCUE IN POLAND – RESEARCH ON SELECTED SPORT COMPETITIONS IN WATER RESCUE - Skalski, D.; Kowalski, D.; Kindzer, B.; Kreft, P.; Grygus, I. (Rehabilitation and Recreation, 2022)
Introduction. Competition is associated with competition. Their main task is to select a team from among the initial teams. In any sports discipline, players are not in to test their skills. Material and methods. The subject of the research are players, rescuers and rescue competitions in the Pomeranian League of Rescue, the 1st round of the Polish Grand Prix and the Summer Polish Championships. Results. The Pomeranian Water Rescue League, despite its short history, enjoys great interest among rescuers. The championship attracted many players from the very beginning. Compared to other professions at a higher level, e.g. The second round of the Polish Grand Prix or the Polish Summer Championship, the number of competitors is very similar, which is a great success of the Pomeranian Water Rescue League. Conclusion. Many people do not finish this competition or are disqualified, which causes many competitors to quit. In addition, the significant lack of equipment in open waters means that many rescuers did not have the opportunity to use specialized equipment, and thus do not have sufficient skills and appropriate training. Consequently, many people skip hardware competitions because they are aware that they do not have enough knowledge and skills in this field.